2007
DOI: 10.1029/2005jd006934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solute dissolution kinetics on cloud droplet formation: Extended Köhler theory

Abstract: [1] This study focuses on the importance of solute dissolution kinetics for cloud droplet formation. To comprehensively account for the kinetics, a numerical model of the process was developed. Simulations of cloud droplet growth were performed for solute diffusivity, droplet growth rates, dry particle and droplet diameters relevant for ambient conditions. Simulations suggest that high ambient supersaturations and low solute diffusivity are major contributors to significant decreases in effective solute surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…In a comprehensive review, Graber and Rudich (2006) concluded that, although it is difficult to distinguish atmospheric HULIS from terrestrial and aquatic humic substances on a chemical level, there are significant differences in physical properties such as hygroscopicity and CCN activity. This has been substantiated in a series of studies on the microphysical properties of HULIS extracted from real aerosol samples (Dinar et al, 2006a(Dinar et al, , b, 2007Asa-Awuku and Nenes, 2007;Taraniuk et al, 2007;Wex et al, 2007). There is indication that HULIS can be of primary origin, e.g., wood combustion, but may also be associated with secondary particle-phase production (Gelencsér et al, 2002;Samburova et al, 2005a, b;Feczko et al, 2007;Surratt et al, 2007aSurratt et al, , 2008.…”
Section: Analysis Of High Molecular Weight Compoundsmentioning
confidence: 88%
“…In a comprehensive review, Graber and Rudich (2006) concluded that, although it is difficult to distinguish atmospheric HULIS from terrestrial and aquatic humic substances on a chemical level, there are significant differences in physical properties such as hygroscopicity and CCN activity. This has been substantiated in a series of studies on the microphysical properties of HULIS extracted from real aerosol samples (Dinar et al, 2006a(Dinar et al, , b, 2007Asa-Awuku and Nenes, 2007;Taraniuk et al, 2007;Wex et al, 2007). There is indication that HULIS can be of primary origin, e.g., wood combustion, but may also be associated with secondary particle-phase production (Gelencsér et al, 2002;Samburova et al, 2005a, b;Feczko et al, 2007;Surratt et al, 2007aSurratt et al, , 2008.…”
Section: Analysis Of High Molecular Weight Compoundsmentioning
confidence: 88%
“…The maximum allowed reduction in σ s is consistent with surface tension measurements of atmospherically relevant organics at relatively dilute solutions (Shulman et al, 1996;Facchini et al, 2000;Tuckermann and Cammenga, 2004;Hyvärinen et al, 2006;Salma et al, 2006;Svenningsson et al, 2006). It should be noted that surface tension is a dynamic parameter which depends on the particle size and relative humidity (Ervens et al, 2005;Asa-Awuku and Nenes, 2007;Dinar et al, 2006). We have assumed, however, that the value of σ s is constant during a model run, i.e.…”
Section: Performed Sensitivity Studiesmentioning
confidence: 99%
“…Recent work has shown that kinetic limitations, including surface films and slow dissolution of particulate substances, can suppress droplet growth (Asa-Awuku and Nenes, 2007;Ruehl et al, 2008). With few exceptions including solute being physically "trapped" within some type of waxy material, dissolution kinetics is governed by diffusion of solute from the solid "core" at the center of a droplet to the growing droplet.…”
Section: Estimated Subsaturated Hygroscopic Growth Factors For the Ormentioning
confidence: 99%
“…With few exceptions including solute being physically "trapped" within some type of waxy material, dissolution kinetics is governed by diffusion of solute from the solid "core" at the center of a droplet to the growing droplet. It has been argued that the latter process is slow enough for compounds with high molecular weights to influence droplet growth kinetics and the Köhler curve (AsaAwuku and Nenes, 2007;Taraniuk et al, 2007;Moore et al, 2008). According to Fig.…”
Section: Estimated Subsaturated Hygroscopic Growth Factors For the Ormentioning
confidence: 99%